2-aminoaethanesulfonic acid compounds possess protective property in reperfusion-induced heart jnjury - Nikolay A. Kurganov; Ekaterina V. Blinova; Elena V. Semeleva; Irina A. Gromova; Dmirty S. Blinov; Andrei V. Novikov; Julija N. Mashkova; Olga V. Vasilkina (Belgorod National Research University, 2018)
The study aim was to explore pharmacological effects of 2-aminoaethansulfonic acid compounds in reperfusion-induced heart injury. Materials and methods. The study was performed on rats and dogs of both sexes, isolated rats' hearts. Two compounds of 2-aminoethanesulfonic acid, magnesium-containing (LBK-527) and phenylacetamide-containing (LKhT-317) were investigated. Antiarrhythmic effects of the compounds were studied in coronary artery reperfusion 7, 30 and 120 min after acute myocardial ischemia modeling. The ability of the substances to limit the volume of reperfusion injury was investigated by differential indicator method. The influence of substances on the intensity of free radical processes in the myocardium, as well as the metabolic profile of coronary venous blood during reperfusion, was studied. Hemodynamic effects of the substances were studied during in vivo experiments, as well as on an isolated heart. Results and discussion. The compounds effectively prevent cardiac arrhythmias generation caused by myocardial reperfusion after 7, 30 and 120 minutes of ischemia. Prophylactic intravenous administration of LHT-317 and LBK-527 at higher therapeutic doses limit the size of rats' heart necrosis zone after occlusion-reperfusion syndrome develops, prevent reperfusion-induced excessive activation of free-radical processes in rat myocardium, activate the antiradical activity of the heart tissues, and optimize [O2] and [CO2] in coronary venous sinus blood of dogs. Cardioprotective effect of the compounds manifests in preserving myocardium contractile function, maintaing BP and stabilizing heart chronotropic function. Conclusions. The study analysis shows that 2-aminoethanesulfonic acid compounds have cardioprotective effect in reperfusion syndrome.